Towards a Pedagogy of the Integration of Clinical Legal Education Within The Law Curriculum: Using De-Identified Clinic Files Within Tutorial Programs - Rachel Spencer; Matthew Atkinson (Legal Education Review)
Pleading drafting is often viewed as a challenging and highly specialised legal skill. This article proposes that pleading drafting exercises can serve as a vehicle for the development of both lawyering skills and more generic transferable skills. It further contends that the skills students can develop through drafting pleadings in law school can help prepare them for legal professional training (LPT), legal practice (practice) or careers outside the law. This article, firstly, examines the nature of pleading drafting and the lawyering and transferable skills it requires. An overview of the experiential learning model and why it is suitable for pleading drafting follows. The pleading drafting activities in the University of Queensland (UQ) Civil Procedure course and relevant results of surveys of the law students who completed those activities in 2012 and 2013 are then analysed. The article concludes that students can benefit in numerous ways from engaging in pleading drafting exercises at a law school level.